Proposed interior design of KZ Kraf retail gallery at PT 4127 and PT 4128, Persiaran Sultan Yusof Izuddin Shah, Lumut, Perak for KZ Kraf Enterprise / Nur Ain Najihah Omar - Omar, Nur Ain Najihah (Faculty of Architecture, Planning and Surveying, 2012)
The final project of final year students for Interior Designs in Diploma level is a manifestation towards the students understanding of every aspect of interior design learned starting from basic until the presentation of the proposal. The project chosen is proposed interior design of KZ Kraf retail and gallery at PT 4127 and PT 4128, Persiaran Sultan Yusof Izuddin Shah, Lumut, Perak for Kz Kraf Enterprise. The site has a potential visitor from local and international come here. Therefore it will help to commercial clay product especially Perak craft which is ‘Labu Sayong’. Research has been conducted to establish this project, including site analysis, interviews, observationsand case study .All this research is to analyze the weakness and find solution for the problem in this project. Base on that, the research will be applied in the process of design which is to attract customer come to the retail and gallery. The mission of the project is to bring a new concept and design idea to encourage people to come and buy the product from retail. It also to give information to visitor about the pottery. The design concept for this project is 'Exquisite Labu Sayong’. This project choose ‘lau sayong’ as metaphore because perak is famous with making labu sayong.